Bimetallic metal-organic framework derived electrocatalyst for efficient overall water splitting. (1st March 2019) - Chen, Zhiming; Xu, Bo; Yang, Xiaodong; Zhang, Haijing; Li, Cuncheng
Abstract: The development of bifunctional catalysts that can be applied to both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is widely regarded as a key factor in the production of sustainable hydrogen fuel by electrochemical water splitting. In this work, we present a high-performance electrocatalyst based on nickel-cobalt metal-organic frameworks for overall water splitting. The as-obtained catalyst shows low overpotential to reaches the current density of 10 mA cm −2 with 249 mV for OER and 143 mV for HER in alkaline media, respectively. More importantly, when the electrolyzer was assembled with the as-prepared catalyst as anode and cathode simultaneously, it demonstrates excellent activity just applies a potential of 1.68 V to achieve 10 mA cm −2 current density for overall water splitting. Graphical abstract: Image 1 Highlights: NiCoSe/C was prepared by direct selenylation of Ni/Co metal-organic framework. The NiCoSe/C catalyst shows high performance for both OER and HER. The NiCoSe/C catalyst shows efficient overall water splitting property.